2019
DOI: 10.1186/s13018-019-1246-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a poloxamer-based thermosensitive gel on rotator cuff repair in a rabbit model: a controlled laboratory study

Abstract: Background A common complication after rotator cuff repair is postoperative stiffness, which can be reduced by a simple application of an anti-adhesive agent. However, anti-adhesive agents may affect rotator cuff healing by preventing fibrosis. This experimental animal study evaluated the effect of the application of a poloxamer-based thermosensitive anti-adhesive gel and its influence on the healing of an acute rotator cuff repair in a rabbit model. Methods Acute rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
10
2
Order By: Relevance
“…11 Antiadhesives have been reported to prevent scar formation in other surgical fields. 5,24,27 However, the prevention of adhesion or scar formation did not lead to improved recovery of functional outcome in the current study. We assumed that in rotator cuff repair, adhesion after the operation is responsible for restricted ROM or recovery.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…11 Antiadhesives have been reported to prevent scar formation in other surgical fields. 5,24,27 However, the prevention of adhesion or scar formation did not lead to improved recovery of functional outcome in the current study. We assumed that in rotator cuff repair, adhesion after the operation is responsible for restricted ROM or recovery.…”
Section: Discussioncontrasting
confidence: 71%
“…12,23 Therefore, the use of antiadhesive agents to reduce postoperative stiffness is becoming more popular. 27,31 However, the current study showed no intergroup difference in the occurrence of postoperative stiffness or recovery of ROM except FF at 6 months postoperatively. Previous studies showed similar results using an antiadhesive agent.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The anti-adhesion effect and safety of Mediclore have been proven in preclinical animal studies [ 27 , 28 ] as well as in clinical studies including transurethral prostate resection (TURP) [ 29 ], total knee arthroplasty [ 30 ], and parotidectomy [ 31 ]. For example, use of Mediclore during TURP in patients with prostatic hyperplasia was significantly associated with a decreased risk of urethral stricture and a higher peak urine flow rate, compared to the instillation of lubricant [ 29 ].…”
Section: Discussionmentioning
confidence: 99%